Широкополосные измерительные сенсоры для анализа электрофизических характеристик влагосодержащих материалов - Буренко, А. В.; Краснощок, В. И.; Бондаренко, И. Н. (ХНУРЕ, 2017)
The content and distribution of free and bound water in moisturecontaining materials of different kind can give almost unlimited information about their properties. In this regard, there is the need to create a broadband measuring sensors for measurements in a wide frequency range. Conducted modeling analysis of the possible use of segments of coaxial and strip lines as sensors of changes in the electrophysical parameters of samples of moisturecontaining materials. The revealed dependences of wave impedance, transmission coefficient, phase shift and attenuation in the considered devices depending on changes in the values of ε and tan δ in the frequency range up to 40 GHz.
Keywords: Измерительные сенсоры; Анализ электрофизических характеристик